ROLE OF PROGESTOGEN-ONLY CONTRACEPTIVES IN WOMEN WITH RISK FACTORS - Haya P., Javier (2015)
There are clinical conditions in which the combined oral contraceptives may involve risks, especially cardiovascular. In these situations the use of progestogen-only contraceptives (APS) could be a good alternative. For example, in women at increased risk of thrombosis, both arterial and venous, using some combination contraceptives may increase the risk of stroke, myocardial infarction or venous thromboembolism, which was not observed with APS. Nor it has described its use increase thrombotic risk in smokers over age 35, as do the combination contraceptives. The AP5 also be a good indication for hypertriglyceridemia, as ethinyl estradiol increases plasma triglyceride levels. Moreover, as with the older and / or the prevalence of obesity risk factors in both conditions may also be suitable to use APS increases. In hypertensive, given the likelihood of increased pressure values induced by estrogen, it is also recommended for use. Its main disadvantage is that they have no proper control of cycles, as given by the combined contraceptive. CONCLUSIONS: progestogen-only contraceptives are a good alternative for women at risk or with contraindications.